Application of Failure Mode and Effects Analysis to Reduce Wastes Power Pole Production Process - Athikulrat, Kittichai; Jangruxsakul, Sirat; Plychumpol, Jedsada (Engineering and Technology Horizons, 2021)
The objective of this research is to reduce wastes in the process of power pole production by means of an application of Failure Mode and Effects Analysis (FMEA) in order to calculate Risk Priority Number (RPN) on purpose to select the failure pattern for improvement. According to the initial study, the results display that there are five failure patterns, encompassing with power pole’s crack, burr, incomplete cast, constricted hole and crooking. Based on those failure ones, the evaluation of severity (withthe brainstorm for investigating the cause) and occurrence from that cause, including detection, in regard to quantity was applied for computing RPN. The consequence of calculation demonstratesthat the maximum RPN of 75 is products exposing failure of crack and burr. The crack was the cause of wire cuttingby employees resulting in non-conforming products, while the burr was the reason for imperfect mold during assembly as well as forgetting to bolt the mold. Accordingly, the measure of improvement was inturn determined. In response, the wire cutting was trained to improve knowledge and skills, whereas the visual control application for enabling those employees to assemble the focus point with perfection. After improvement, the outcome is exhibited that wastes are reduced by 11.93%. (decreased from 2.43 to 2.14%). Meanwhile, RPNs in relation to the failure of crack and burrare decreased to 30 and 18, respectively